Sinonichnus gen. n. for Scydmoraphes yunnanensis Jałoszyński, and description of Sinonichnus leiodicornutus sp. n. (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
Scydmoraphes yunnanensis Jałoszyński shows several unusual characters as for a member of this broadly distributed Palaearctic genus. Discovery of this species in a new locality and several newly available specimens allowed for detailed morphological study. As a result, a new genus, Sinonichnus gen. n., is established to accommodate Sinonichnus yunnanensis comb. n., and another species, showing unusual modifications of the male antennae, Sinonichnus leiodicornutus sp. n. Both species are known to occur in Yunnan, China. Sinonichnus is the first known Stenichnini genus that combines the presence of the pre-tentorial gular sutures with the prosternum laterally fused with inner regions of hypomera; all remaining world genera that show the gular sutures between posterior tentorial pits and the posteromesal margins of cardines have the prosterna demarcated laterally by notosternal sutures. An updated identification key to Eurasian Stenichnini genera whose adults have the pre-tentorial gular sutures is given.